ASSESSMENT OF SEISMIC INFLUENCES IN THE PROJECT OF STATE BUILDING CODES - KENDZERA, O.; LISOVYI, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The problem of seismic influences assessment at building of habitation and important objects is considered. A necessity of modification in building codes for description of seismic hazard in physical units (accelerations, velocities, displacements) which characterize seismic motions on construction sites is shown. Carrying out such modification is possible only on the basis of analysis of parameters of the real seismic shakings from the local and remote earthquakes. For reliable estimation of seismic danger on the territory of Ukraine, it is necessary to found the network of the seismic stations provide with a modern digital seismological equipments. It will allow providing a reliable protection of habitations, industrial structures, especially important and ecologically dangerous objects.